1996
DOI: 10.1093/carcin/17.3.595
|View full text |Cite
|
Sign up to set email alerts
|

p53 and Ha-ras mutations in chemically induced hamster buccal pouch carcinomas

Abstract: Well-differentiated squamous cell carcinomas were induced in hamster buccal pouch epithelium by twice weekly topical applications of N-methyl-N-benzylnitrosamine (MBN) or 7,12-dimethylbenz[a]anthracene (DMBA) over a period of 15 weeks. Each of the 22 tumors induced (14 MBN and eight DMBA) were evaluated by single-strand conformation polymorphism and DNA sequencing to identify mutations in conserved exons (E5-E8) of the p53 tumor suppressor gene and codons 12/13 and 61 of Ha-ras. In addition, Northern blot anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
4

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 34 publications
2
21
0
4
Order By: Relevance
“…Examples are chemically induced squamous cell carcinomas of the bucal pouch in hamster where seven of 22 tumors contained p53 mutations but none showed overexpression of Mdm2 mRNA (Chang et al, 1996) and pancreatic duct adenocarcinomas where Âźve of 19 tumors contained higher Mdm2 mRNA levels but none had p53 mutations (Chang et al, 1995). This kind of tumor type speciÂźcity also suggests that p53 mutation and Mdm2 overexpression are phenotypically not equivalent, although one cannot exclude that this speciÂźcity is rather a reÂŻection of the type of mutations occurring in di erent tumors (point mutations for p53 versus gene ampliÂźcations for Mdm2).…”
Section: Mdm2 Gene Structure and Expressionmentioning
confidence: 99%
“…Examples are chemically induced squamous cell carcinomas of the bucal pouch in hamster where seven of 22 tumors contained p53 mutations but none showed overexpression of Mdm2 mRNA (Chang et al, 1996) and pancreatic duct adenocarcinomas where Âźve of 19 tumors contained higher Mdm2 mRNA levels but none had p53 mutations (Chang et al, 1995). This kind of tumor type speciÂźcity also suggests that p53 mutation and Mdm2 overexpression are phenotypically not equivalent, although one cannot exclude that this speciÂźcity is rather a reÂŻection of the type of mutations occurring in di erent tumors (point mutations for p53 versus gene ampliÂźcations for Mdm2).…”
Section: Mdm2 Gene Structure and Expressionmentioning
confidence: 99%
“…Squamous cell carcinomas induced by the application of 7,12-dimethylbenz[a]anthracene (DMBA) to the cheek pouch of the Syrian hamsters are morphologically and histologically similar to human tumours [10,11]. In addition, hamster tumours express many metabolic and molecular markers that are expressed in human oral cancer [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent types of p53 mutation found in Taiwanese OSCCs were G:C to A:T transitions and G:C to T:A transversions. Studies have demonstrated that these types of mutations are the most common mutations observed in animals treated with NNK or other tobacco nitrosamines (Belinsky et al, 1991;Oreffo et al, 1993;Ronai et al, 1993;Chang et al, 1996). Evidence from the literature also indicates that NNK-associated DNA adducts, in addition to being repaired by the nucleotide excision repair pathway, are also repaired by base excision repair (Cloutier and Castonguay, 1998).…”
mentioning
confidence: 99%